Multimodal Imaging of Acquired Vitelliform Lesion Diagnosed at Pseudohypopyon Stage - Nuno Moreira Gonçalves; Ângela M. Carneiro; Elisete Brandão; Fernando M. Falcão-Reis (Case Reports in Ophthalmological Medicine)
Purpose. To present a case study of a monocular acquired vitelliform lesion, studied with multimodal fundus imaging (spectral-domain-optical coherence tomography, fundus autofluorescence, and fluorescein angiography) with a followup of three years. Case Report. An asymptomatic macular lesion was detected on a 64-year-old man. Fundus exam revealed a macular lesion with an apparent horizontal level associated with multiple round small whitish lesions, suggestive of cuticular drusen. He was studied with autofluorescence of the fundus (FAF), fluorescein angiography (FA), spectral domain-optical coherence tomography (SD-OCT), and electrooculogram. The findings were compatible with the diagnosis of acquired vitelliform lesion, associated with cuticular drusen. After one year, the visual acuity decreased to 20/50, without identifiable alterations of the FAF, FA, or SD-OCT. Three years later, fundoscopy and imaging showed an evolution to a state similar to vitelli disruptive phase of Best disease with an improvement of visual acuity to 20/25. We report the results of FAF, FA, and SD-OCT at this stage. Conclusion. Acquired vitelliform lesions associated with cuticular drusen can present as a pseudohypopyon lesion, and the evolution to the atrophic phase can be associated with an improvement of visual acuity.